Analysis of the openings of aircraft composite laminated wing beam web under shear load. Issue 1 (1st April 2022) - Zhang, X L; Wang, J C; Xu, Q; Wang, Y Y; Li, C Y
Abstract: In this paper, experiments and finite element methods are used to study the openings of the composite wing spar web of a civil aircraft. First, according to the design principles of composite laminates, determine the layup sequence and layup ratio of the spar, and then lay the beam webs and the beam edge strips integrally; then, calculate the equivalent of the spar by using the classic laminate theory Material properties, the method to calculate the equivalent elastic modulus of composite laminates of different thicknesses is derived; then, the influence of opening shape and opening angle on the strength of composite wing spar web under shear load is analyzed. Finally, the reinforcement design is carried out on the opening position. This research method not only solves specific engineering design problems, but also proposes a set of practical, cost-effective and efficient design methods for composite material opening shapes, which has a certain generality. Its design ideas and methods provide technical support for civil aircraft structural design.